Challenges and Prospects of Implementing eGovernance in Nigeria - Nchuchuwe, PhD, Francis F.; David, Ojo Ann (Covenant University Journal of Politics and International Affairs, 2016)
By the turn of the 21 st century, the world moved towards a new era called the Information Age. This was occasioned by the upsurge, endeavour in most countries of the world, in the use of information and communications technology in virtually all facets of human. From basic activities like acquiring knowledge and conducting research to mailing of letters to friends, carrying out business transactions, among others, the use of the internet and other related electronic devices has become the dominant means through which an individual, or a firm can reach out to one person, or a group of persons, or the entire globe, just by a push of a button. Many government organizations have since keyed into this phenomenon. This gave rise to the use of such prefix as â€œE-â€œ, which implies â€œElectronicâ€, to complement governance in governmental organizations that have adopted its use. Some states and government parastatals in Nigeria for example, Lagos State has since embraced the concept. This paper therefore examines the challenges its implementation in Nigeria would pose. It takes a cursory look at the processes involved and relating it with Nigerian environment and concludes that for success to be achieved, the following should be in place; a purposeful leader willing to embrace e-governance as a matter of government policy, creating more and effective cyber laws and cafes, making deliberate and concerted plans for training on the effective use of machineries and equipments necessary for e -Governance ,provision of adequate funds for hard wares and soft wares, establishing of community e-centers, and providing easily accessible websites of government and non governmental agencies among others.